Analysis of the Effectiveness of Utilization of Regional Owned-Asset to Increase Regional Revenue - Zulfita Fidi Astuti; Santoso Tri Hananto; Andi Asrihapsari (JRAK: Journal of Accounting Research and Computerized Accounting, 2024)
Utilization of Regional Owned-Asset (Indonesian: Barang Milik Daerah, abbreviated BMD) is one of the opportunities for regions to increase Original Local Government Revenue (Indonesian: Pendapatan Asli Daerah, abbreviated PAD). This study aims at analyzing the effectiveness of implementing BMD utilization to increase PAD. It is a case study at Regional Income and Asset Financial Management Agency (Indonesian: Badan Pengelolaan Keuangan dan Aset Daerah, abbreviated BPKAD) Surakarta. A qualitative descriptive approach is employed in this study. The data are in the form of primary and secondary data and were obtained from the data of the utilization of BMD that has been implemented and reports on the realization of regional income and expenditure budgets. The results of this study show that BMD utilization in Surakarta is implemented effectively although it is still not optimal. The utilization of BMD has contributed to PAD Surakarta by showing an increase every year. Even though it has increased, the contribution of the use of BMD to PAD is little, which is under one percent of all other PAD components. Surakarta government needs to optimize the use of BMD and innovations or groundbreaking ideas to increase the contribution rate to Surakarta's PAD.